Perlindungan Hukum Terhadap Warga Negara Indonesia Atas Tuduhan Penyebar Hoax Covid-19 Ditinjau Dari Perspektif Hak Asasi Manusia - Monang Pulungan, Rynaldi (Journal Evidence Of Law, 2023)
Information technology plays a crucial role in the modern era. The rapid advancement of information technology has various complex implications for daily human activities. However, despite the positive impact of the increasing number of internet users on human life, there are also negative consequences that can harm individuals, society, and the country. Currently, Indonesia is facing the widespread coronavirus outbreak, with its origin still unknown. This new disease, known as Covid-19, is highly dangerous as it can quickly transmit from one human to another and even through environmental objects. Regarding the dissemination of false information or hoaxes, it is important to address statements made by government officials and elites that tend to downplay or suggest that Indonesia is immune to virus attacks, or the dissemination of baseless information. Such statements contradict the obligation to provide accurate information as stipulated in various regulations, such as Article 154 Jo. 155 of Law no. 36 of 2009 concerning Health. Regrettably, in light of the events observed in this study, concerns about the spread of hoaxes are not accompanied by efforts to establish reliable and comprehensive communication and public information channels from the government.